STRATEGI ELEKTRONIK WORD OF MOUTH DALAM MENINGKATKAN PENJUALAN PADA SHEREN HIJAB BENGKULU - Andang Sunarto; Andi Harpepen; Rossella Afriani (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2024)
The purpose of this study was to determine the Electronic word of mouth strategy in increasing sales at Sheren Hijab Bengkulu. This type of research is field research (Field research). This study uses a qualitative research approach. Data collection techniques were carried out by observation, interviews and documentation. Data analysis techniques using data reduction, data presentation and drawing and testing conclusions. The results of this study are that the Elektronik word of mouth strategy in increasing sales at Sheren Hijab Bengkulu has been carried out correctly by determining the target market because we cannot sell products to everyone. By creating a product marketing strategy, Sheren Hijab can determine a more specific and clearer target market. Sheren Hijab always reviews products with interesting content to sell. So that the comments column on social networks has a lot of positive comments.